Facile Preparation of Cost‐Effective Triphenylamine‐Based Nanoporous Organic Polymers for CO2, I2, and Organic Solvents Capture. Issue 14 (22nd April 2022) - Yan, Jun; Guo, Yide; Xie, Siyu; Wang, Qilin; Leng, Zesong; Li, Dan; Qi, Kangru; Sun, Haiyu
Abstract: Seeking cost‐effective construction of nanoporous organic polymers for CO2 and I2 capture and organic solvents adsorption remains challenging. Two triphenylamine‐based nanoporous organic polymers, ANOP‐1 and ANOP‐2, have been prepared successfully by Friedel–Crafts (F–C) hydroxyalkylation from low‐cost triphenylamine (TPA) with commercial terephthalaldehyde and isophthalaldehyde, respectively. The effect of isomers of phenyl dialdehydes on the structure of porous architecture is investigated. The as‐prepared ANOPs exhibit a moderate uptake of CO2, I2, and organic solvents because of the electron‐rich TPA unit and nanometer‐scale pore size of <2 nm. These findings demonstrate that F–C hydroxyalkylation is a cost‐effective strategy for producing large amounts of triphenylamine‐enriched, high specific BET surface area materials to develop commercial organic materials for industrial use. Abstract : The commercial terephthalaldehyde and isophthalaldehyde are used to react with inexpensive triphenylamine respectively to yield two triphenylamine‐based nanoporous organic polymers, ANOP‐1 and ANOP‐2. The influence of isomers of phenyl dialdehydes on the structure of porous architecture is investigated. The resultant ANOPs exhibit a moderate uptake of CO2, I2, and organic solvents.